Kinerja Lingkungan dan Biaya Lingkungan: Faktor Penentu Nilai Perusahaan di Era Keberlanjutan - Rahma Ayu Pertiwi; Indira Januarti (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to examine the effects of environmental performance and environmental costs on the firm value of manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2023. A quantitative method was employed using multiple linear regression analysis. The findings reveal that environmental performance does not have a significant impact on firm value, while environmental costs have a substantial negative effect. These results imply that corporate efforts to improve environmental performance have not directly contributed to an increase in market value, whereas the financial burden arising from high environmental expenditures may lead to a decline in company valuation. This study provides insights into the interaction between environmental sustainability and firm valuation, offering valuable implications for managerial strategies and investment decisions.